Public Policy, Vested Interest, and Common People in Brazil in the Twenty-First Century. Issue 2 (3rd April 2017) - Gambus, Ivan; Almeida, Felipe
Abstract: We offer an original institutional approach to analyzing policies meant to regulate the actions of common people in the Brazilian state agenda in recent years. We also address the reactions of vested interests against this agenda. Such vested interests rely on corporations' ceremonial encapsulation of state policies — policies that were established during the decades when Brazil's industrialization process took place. Brazilian policies for the common people, however, are a twenty-first-century phenomenon.